(untitled) (Epidemiology, Biostatistics, and Public Health, 2022)
Background: Physical activity (PA) in adolescence with long term illnesses or disabilities (LTID) is a public health concern. One way of increasing PA is through participation in sports clubs. Since sports clubs are organised and regular, there are expected to be differences in motivation for physical activity between adolescents that are members and non-members. The purpose of this study is to assess the impact of psychosocial factors on sports club membership and daily PA. Methods: Finnish adolescents with self-reported LTID (n=1006) took part in the WHO collaborative Health Behaviour in School-aged Children (HBSC) study in 2002 and 2010. Daily self-reported moderate to vigorous PA (MVPA) was the outcome variable. Psychosocial variables included intention for future PA, self-perceptions, and educational aspirations. Age and sports club membership was included in binary logistic regression analyses Analyses were done separately for boys and girls. Results: Adolescents with LTID who were sports club members were two times more likely to be active daily than non-members. However, for girls, there was no significant difference between members and non-members. Moreover, definite intention for future PA, higher self-perceptions, and educational aspirations to other education or training than general upper secondary school were significant predictors. Conclusions: Adolescents with LTID need encouragement to be active daily. One possible way to achieve this is through sports club participation. Implementing adaptive motivating techniques in sports clubs is especially important for girls in clubs. More research is needed on the associations of daily MVPA with different educational aspirations for adolescents with LTID.